ThinSight: versatile multi-touch sensing for thin form-factor displays - Hodges, Steve; Izadi, Shahram; Butler, Alex; Rrustemi, Alban; Buxton, Bill (UIST '07: Proceedings of the 20th annual ACM symposium on User interface software and technology, Newport, Rhode Island, USA, 2007)
ThinSight is a novel optical sensing system, fully integrated into a thin form factor display, capable of detecting multiple fingers placed on or near the display surface. We describe this new hardware in detail, and demonstrate how it can be embedded behind a regular LCD, allowing sensing without degradation of display capability. With our approach, fingertips and hands are clearly identifiable through the display, allowing zero force multi-touch interaction. The approach of optical sensing also opens up the possibility for detecting other physical objects and visual markers through the display, and some initial experiments with these are described. A major advantage of ThinSight over existing camera and projector based optical systems is its compact, thin form-factor making it easier to deploy. We therefore envisage using this approach to capture rich sensor data through the display to enable both multi-touch and tangible interaction. We also discuss other novel capabilities of our system including interacting with the display from a distance and direct bidirectional communication between the display and mobile devices.